A missing link between facilitation and plant species coexistence: nurses benefit generally rare species more than common ones. (17th July 2015) - Soliveres, Santiago; Maestre, Fernando T.; Berdugo, Miguel; Allan, Eric; Wilson, Scott
Summary Positive interactions among plants can increase species richness by relaxing environmental filters and providing more heterogeneous environments. However, it is not known if facilitation could affect coexistence through other mechanisms. Most studies on plant coexistence focus on negative frequency‐dependent mechanisms (decreasing the abundance of common species); here, we test if facilitation can enhance coexistence by giving species an advantage when rare. To test our hypothesis, we used a global data set from drylands and alpine environments and measured the intensity of facilitation (based on co‐occurrences with nurse plants) for 48 species present in at least 4 different sites and with a range of abundances in the field. We compared these results with the degree of facilitation experienced by species which are globally rare or common (according to the IUCN Red List), and with a larger data base including over 1200 co‐occurrences of target species with their nurses. Facilitation was stronger for rare species (i.e. those having lower local abundances or considered endangered by the IUCN) than for common species, and strongly decreased with the abundance of the facilitated species. These results hold after accounting for the distance of each species from its ecological optimum (i.e. the degree of functional stress it experiences). Synthesis. Our results highlight that nurse plants not only increase the number of species able to colonize a given site, but may also promote species coexistence by preventing the local extinction of rare species. Our findings illustrate the role that nurse plants play in conserving endangered species and link the relationship between facilitation and diversity with coexistence theory. As such, they provide further mechanistic understanding on how facilitation maintains plant diversity.